Nilai Civic Culture pada Tradisi Kematian Pahamang di Desa Kondamara Kabupaten Sumba Timur - Tinggi Nalu, Syarifah; Sumardi, Lalu; Basyariah, Basyariah; Sawaludin, Sawaludin (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
Indonesia’s diverse cultures preserve rich traditions and noble values, particularly in funeral customs, which vary across ethnic and religious communities but share common ceremonial elements. One such tradition is Pahamang, a funeral ritual practiced by the people of East Sumba. This study aims to describe the Pahamang process and examine the civic culture values embedded within it. Employing a qualitative approach with an ethnographic method, data were collected through interviews, observations, and documentation. The data were analyzed through data condensation, display, and conclusion drawing. The findings indicate that Pahamang consists of three stages: preparation, implementation, and closing. While its core structure remains, notable differences have emerged between the ancient and modern practices. The tradition reflects several civic culture values, including responsibility, mutual cooperation, democracy, kinship, and solidarity, which serve to strengthen social ties within the community. This research offers valuable insights into how local wisdom and traditional rituals contribute to the development of civic values and community resilience in a rapidly modernizing society.